2007
DOI: 10.1165/rcmb.2006-0064oc
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Ion Transport of Human Nasal Polyp and Paranasal Sinus Mucosa

Abstract: Nasal cavity and paranasal sinus have various functions. However, little information is available on ion transport in these upper airway epithelia. In the present study, we measured the anion secretion and the anion channel activity to characterize the ion transport in epithelial cells prepared from human paranasal sinus mucosa (PSM) and nasal polyp (NP). To estimate the anion secretion and the anion channel activity, we measured the short-circuit current (Isc) and the transepithelial conductance (Gt) sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…Yasuda et al mentioned that epithelium of paranasal sinus mucosa would secrete water and maintain ASL covering upper airway using cultured nasal epithelium. (10) We demonstrated that application of L-ascorbate to the surface of freshly excised sinonasal tissue stimulated Cl secretion in a sustained fashion to 70% (in sinus epithelium from CRS) and 53.6% (in nasal epithelium from CRS) of Cl currents elicited at maximally stimulated cAMP levels using 20 µM forskolin. Our data using freshly excised human tissue supports that the source of moisture in the nasal cavity may come from the epithelium of paranasal sinuses.…”
Section: Discussionmentioning
confidence: 90%
“…Yasuda et al mentioned that epithelium of paranasal sinus mucosa would secrete water and maintain ASL covering upper airway using cultured nasal epithelium. (10) We demonstrated that application of L-ascorbate to the surface of freshly excised sinonasal tissue stimulated Cl secretion in a sustained fashion to 70% (in sinus epithelium from CRS) and 53.6% (in nasal epithelium from CRS) of Cl currents elicited at maximally stimulated cAMP levels using 20 µM forskolin. Our data using freshly excised human tissue supports that the source of moisture in the nasal cavity may come from the epithelium of paranasal sinuses.…”
Section: Discussionmentioning
confidence: 90%
“…Transepithelial potential (PD) was continuously measured by a high-impedance millivoltmeter that could function as a voltage clamp with automatic fluid resistance compensation (VCC-600, Physiologic Instruments, San Diego, CA) with a pair of calomel electrodes that were immersed in a saturated KCl solution and bridged to the modified Ussing chamber by a pair of polyethylene tubes filled with a solution of 2% (wt/vol) agarose in a 2 M KCl solution (18,19,22,38). I sc was measured by the amplifier (VCC-600) with a pair of silver-silver chloride electrodes that were immersed in a 2 M NaCl solution and bridged to the modified Ussing chamber by a pair of polyethylene tubes filled with a solution of 2% (wt/vol) agarose in a 2 M NaCl solution (1,(42)(43)(44). When the I sc was measured, the PD was clamped to 0 mV for 1 s by the amplifier.…”
Section: Measurement Of Iscmentioning
confidence: 99%
“…Monolayers of cells subcultured were rinsed on tissue culture-treated Transwell filter cups with solution A, which were transferred to a modified Ussing chamber (Jim's Instrument, Iowa City, IA, USA) designed to hold the filter cup. Gp, G Na (Na þ -selective Gp) and G Cl (Cl À -selective Gp) were measured and calculated in the presence of 10 mM benzamil, a specific blocker of ENaC (Eaton and Marunaka, 1990;Kleyman and Cragoe, 1990), 300 mM NPPB, a blocker of Cl À channel (Wangemann et al, 1986;Yasuda et al, 2007a) and 1 mM BaCl 2 , a blocker of the K þ channel (Hanrahan et al, 1986) in the apical solution. Transepithelial conductance (Gt) was done by the previously reported method (Niisato et al, 2004aYasuda et al, 2007a,b) of continuously measuring the transepithelial potential (Vt) with a high-impedance milivoltmeter that could function as a voltage clamp with automatic fluid resistance compensation (VCC-600, Physiologic Instrument, San Diego, CA, USA) (Fujimoto et al, 2005;Hasegawa et al, 2006;Niisato et al, 2007c;Taruno et al, 2008;Ueda-Nishimura et al, 2005).…”
Section: Measurement Of Paracellular Ion Conductancementioning
confidence: 99%
“…Transepithelial conductance (Gt) was done by the previously reported method (Niisato et al, 2004aYasuda et al, 2007a,b) of continuously measuring the transepithelial potential (Vt) with a high-impedance milivoltmeter that could function as a voltage clamp with automatic fluid resistance compensation (VCC-600, Physiologic Instrument, San Diego, CA, USA) (Fujimoto et al, 2005;Hasegawa et al, 2006;Niisato et al, 2007c;Taruno et al, 2008;Ueda-Nishimura et al, 2005). Gp, G Na (Na þ -selective Gp) and G Cl (Cl À -selective Gp) were measured and calculated in the presence of 10 mM benzamil, a specific blocker of ENaC (Eaton and Marunaka, 1990;Kleyman and Cragoe, 1990), 300 mM NPPB, a blocker of Cl À channel (Wangemann et al, 1986;Yasuda et al, 2007a) and 1 mM BaCl 2 , a blocker of the K þ channel (Hanrahan et al, 1986) in the apical solution. Application of these agents to the apical solution abolished the Isc from 0.82 AE 0.0 to 0.00 AE 0.0 mA/cm 2 (mean AE S.E., p < 0.00001, n ¼ 169), and diminished the Gt from 91.4 AE 1.36 to 72.6 AE 1.3 mS/cm 2 (mean AE S.E., p < 0.00001, n ¼ 169; Tokuda et al, 2007).…”
Section: Measurement Of Paracellular Ion Conductancementioning
confidence: 99%